Investigation of Potential Distribution and the Influence of Ion Complexation on Diffusion Potentials at Aqueous-Aqueous Boundaries within a Dual-Stream Microfluidic Structure - Strutwolf, J.; Manning, M.; Arrigan, Damien (American Chemical Society, 2009)
The occurrence of reactions at boundaries between adjacentmiscible but unmixed aqueous streams coflowing ina microfluidic channel structure has been studied bysimulation of the diffusion potentials that develop betweenthe two coflowing aqueous electrolyte streams and bymeasurement of the effects of aqueous ion complexationon diffusion potentials. The microfluidic structure consistedof a Y-shaped microchannel with off-chip electrodesimmersed in electrolyte reservoirs connected by capillariesto the Y-microchannel. The time-dependent, onedimensionalNernst-Planck equation employing the electroneutralitycondition was solved numerically to calculatethe diffusion potentials established at the boundarybetween the two coflowing aqueous streams. Under theexperimental conditions (channel length and width, flowrate) employed, it was shown that the use of the Hendersonequation was appropriate. It was also shown thatthe cross-channel diffusion potential remained constantfrom the entrance of the channel to the exit. The influenceof cation complexation by a neutral ionophore was investigatedby experimentally measured diffusion potentials.It was found that potassium complexation by the cyclicpolyether 18-crown-6 altered the experimental diffusionpotential, whereas the interaction of sodium or lithiumcations with the ionophore did not perturb the diffusionpotential. The results are consistent with the literaturedata for aqueous-phase complexation of these cations bythis ionophore. The results of these investigations demonstratethat relatively simple diffusion potential measurementsbetween coflowing streams in microchannelsmay be used as a basis for study of ion complexationreactions occurring at boundaries between miscible fluids.